Existence of Human Rights Protection in Land and Mining Conflicts: Evidence from Indonesia - Hanum, Willy Naresta; Zaman, Muhamad Nafi Uz (Journal of Law, Environmental and Justice, 2024)
Human rights should not be subject to reduction under any circumstances except where such reductions are explicitly justified by law. In agrarian conflicts, regulations governing land acquisition may infringe upon individuals' fundamental rights, including land ownership rights, in the name of public interest. However, the extent to which the law can diminish the fundamental rights of citizens remains a subject of ongoing debate. This study explores how human rights can be preserved in agrarian conflicts, particularly those involving land acquisition for public interest, followed by mining disputes.  This doctrinal research employs a statutory, conceptual, and case study approach. The findings indicate that human rights in land and mining conflicts can be upheld if there is alignment between legal frameworks, the actions of field officers, and the idealism of judges in making rulings that prioritize protecting human rights. Moreover, the concept of land acquisition for public interest should not be construed as automatically granting the government the right to repurpose land for other purposes, even when such purposes are related to the primary objective of the land acquisition.